Open pilot trial of a brief motivational interviewing-based HIV pre-exposure prophylaxis intervention for men who have sex with men: preliminary effects, and evidence of feasibility and acceptability. Issue 3 (3rd March 2020) - Moitra, Ethan; van den Berg, Jacob J.; Sowemimo-Coker, Genoviva; Chau, Sathiarith; Nunn, Amy; Chan, Philip A.
ABSTRACT: Gay, bisexual and other men who have sex with men (MSM) are at high-risk of HIV infection in the United States. Daily oral pre-exposure prophylaxis (PrEP) has demonstrated efficacy in reducing HIV acquisition among MSM. However, PrEP uptake in real-world clinical settings has been slow and uneven. Guided by Self-Regulation Theory, we developed and evaluated a brief (15–25 min) motivational interviewing (MI)-based intervention to promote PrEP uptake in an uncontrolled pilot trial. Nineteen MSM were recruited during the course of routine HIV screening at a sexually transmitted diseases clinic. We administered the 2-session intervention in-person and by telephone. Thirteen (72%) participants completed baseline and 1-month follow-up assessments; all found the intervention and its components highly acceptable. Over the 1-month period, seven participants (37%) obtained a PrEP prescription, more than tripling the rate previously observed with PrEP counseling and referrals alone (11%). The most common barrier to uptake was out-of-pocket costs. This approach was feasible and underscored the need for financial assistance and other PrEP navigation services to supplement behavioral interventions to enhance PrEP uptake.